Development of Strand Burner Test by Using Aluminized AP/HTPB - Mohammad Hafizi, Jamaluddin; R., Mamat; Amir, Aziz; M. M., Noor; Ahmad Tamimi, Ahmad Termizi (Trans Tech Publications Ltd, 2017)
One of the key factors that play an important role in the performance of a solid propellant rocket is dependent on its burning rate. A strand burner is a type of apparatus used to measure the propellant burning rate at elevated pressure. This study investigates the relation between burning rates of aluminized ammonium perchlorate at low pressure. Chamber pressure was varied from 1 atm, 3 atm, 5 atm and 7 atm. This study shows that propellant burning rate is about 50%-62% higher when the burn rate test is conducted at atmospheric condition compared to when it is done in inert gas. The investigation’s results also revealed an increasing propellant burning rate when the chamber pressure is increased. In conclusion, the burning condition and chamber pressure influences the propellant burning rate.